Would Waiting Time Influences Customer Satisfaction Towards Services Patronage A Study Of Lembaga Tabung Haji - Abd. Aziz, Sumaiyah (2004)
This study investigates on the impact of waiting time perspective towards customer satisfaction before being served at the service counter.